A Report of Two Cases of Hazards Associated with High Flow Arteriovenous Fistula in ESRD Patients. (10th April 2018) - Shah, Vipuj; Navuluri, Rakesh; Becker, Yolanda; Hammes, Mary
Abstract : High flow arteriovenous fistulas are a common clinical entity affecting patients with end-stage renal failure receiving hemodialysis. Given the difficulty in predicting who will develop a high flow arteriovenous fistula the exact prevalence is unclear. We present two cases of patients with high flow arteriovenous fistula that developed clinical cardiac failure at a time point after the fistula was placed with findings of significant cephalic arch stenosis. Both patients required treatment of cephalic arch stenosis with balloon angioplasty with subsequent surgical aneurism resection. Accurate and timely diagnosis of high flow arteriovenous hemodynamics by prospective monitoring of volumetric flow and cardiac function is required to halt this process prior to cardiac compromise.